Usaba Sumbu; Potensi Wisata Budaya Dan Wisata Gastronomi Di Kabupaten Karangasem - Dewa Ayu Carma Citrawati; I Gede Gita Purnama Arsa Putra (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2021)
Cultural and gastronomic tourism are potential options to be developed in Timbrah Traditional Village, Karangasem Regency. The Timbrah Traditional Village has a Usaba Sumbu ceremony which is held once a year with a procession that takes up to one week. The potential for implementing Usaba Sumbu as a tourist destination can be seen from the cultural attractions, culinary activities carried out by the community, as well as the potential for the development of craft crafts of the Timbrah traditional village community. The various cultural components summarized in Usaba Sumbu are utilized and supported by adequate accessibility, supporting facilities and supporting services.Keywords, Usaba Sumbu, cultural tourism, gastronomic tourism